2021
DOI: 10.3389/fonc.2021.698946
|View full text |Cite
|
Sign up to set email alerts
|

Role of Sex in the Therapeutic Targeting of p53 Circuitry

Abstract: Sex profoundly affects cancer incidence and susceptibility to therapy, with sex hormones highly contributing to this disparity. Various studies and omics data suggest a relationship between sex and the oncosuppressor p53 circuitry, including its regulators MDM2 and MDM4. Association of this network with genetic variation underlies sex-related altered cancer risk, age of onset, and cancer sensitivity to therapy. Moreover, sex-related factors, mainly estrogenic hormones, can affect the levels and/or function of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 113 publications
(142 reference statements)
0
3
0
Order By: Relevance
“…MDMX could be involved in the reprogramming of fetal macrophages (HC) during preeclampsia and other gestational complications and labor. Drawing from the breast cancer literature [ 72 ], downregulation of placental MDMX in preeclampsia could be linked to estrogen receptor-α [ 73 ] and lower estrogen levels [ 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…MDMX could be involved in the reprogramming of fetal macrophages (HC) during preeclampsia and other gestational complications and labor. Drawing from the breast cancer literature [ 72 ], downregulation of placental MDMX in preeclampsia could be linked to estrogen receptor-α [ 73 ] and lower estrogen levels [ 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…MDMX could be involved in the reprogramming of fetal macrophages (HC) during preeclampsia and other gestational complications and labor. Drawing from the breast cancer literature 70 , downregulation of placental MDMX in preeclampsia could be linked to estrogen receptor-α 71 and lower estrogen levels 72,73 .…”
Section: And Transmission Electron Microscopy Images In a Study At Tw...mentioning
confidence: 99%
“…There is accumulating evidence that genes and proteins are differentially expressed between males and females. For example, genomics studies have linked sex with p53 and MDM2/4 mutations [86]. Another study that focuses on understanding why Kaposi sarcoma-associated herpesvirus preferentially infects and causes Kaposi sarcoma in males suggested that the androgen receptor is a functional prerequisite for cell invasion by Kaposi sarcoma-associated herpesvirus [87].…”
Section: Genomicsmentioning
confidence: 99%